Volcanic geoheritage in Arequipa, Southern Peru: Assessment of pilot geosites for geohazard resilience - Arias Salazar, Carla (2025)
Arequipa, often referred to as “White City, land of volcanoes,” is located in Southern Peru and is a designated UNESCO World Heritage Site. Its amazing landscape is framed by three imposing volcanoes: Chachani, Misti, and Pichu Pichu, reflecting a rich volcanic history evident in several geological sites both within and around the city. A total of 12 pilot geosites related to Chachani and Misti volcanoes, as well as Yura monogenetic field, have been inventoried and assessed. These encompass a range of volcanic deposits, structures, and scenic viewpoints, and have been classified based on their scientific, educational, and touristic value. The selection of these geosites was based on multiple criteria to ensure objectivity, prioritizing those that are the most representative, unique, in good conservation status, and of great scientific importance. Additionally, degradation risks have been evaluated to implement appropriate geoconservation measures and address potential threats according to their urgency. The assessment has followed a holistic methodology, inspired by successful models from previous studies, and recommendations have been made for developing an integrated management plan. The next step is to prepare the geosites for public use by developing geo-routes that highlight the volcanic geoheritage, while also integrating Arequipa's historical and cultural legacy. These geosites play a crucial role in geoeducation, raising awareness about volcanology and volcanic hazards. Moreover, the development of geotourism as a sustainable natural resource not only brings socioeconomic benefits to the local population but also fosters a deeper connection and identity with the territory. This enhanced sense of belonging strengthens community resilience to geological hazards, enabling better preparedness and adaptive strategies in the face of potential risks.